(untitled) (Fiep Bulletin - online, 2014)
The importance of sports in Brazil is colonial. Used as a way for disciplinary control labor, political influence, educational and even source of profit, the sports activity was developed through out centuries. Despite making itself maidenly present in other constitutions, it was the “Citizenin” Constituition 1988 that brought sports to the level it was due. The same. This same device allows exceptional autonomy in § 2º granted to the Legal Organizations: "The Justice will only admit actions related to discipline in sports competitions after exhausting all instances of the sports court, set by law. However, such autonomy is not complete. The constitution itself admits interventions in legal decisions in sports. The problem, therefore, arises The study`s objective, thus, is to analyze where the Sports Justice is, in fact, autonomous and how affecting and at the same time fundamental the common Justice `s intervention can be.